Pengaruh Capital Adequacy Ratio (Car) Terhadap Perubahan Laba Pada Pt. Bank Tabungan Negara (Btn), Tbk - Fia Dialysa (Universitas Islam Bandung, 2017)
The economic crisis that hit Indonesia at this time, one of them caused by the weakening of the Rupiah against the United States dollar (US). The situation is affecting all aspects of the economy. There were changes in profit declined due to high operating costs, minimum capital adequacy, and the level of leverage that can not be predicted. This led banks became less competitive in the era of the Asean Economic Community.The purpose of this study was to determine effect of Capital Adequacy Ratio (CAR) to Profit Changes in PT. Bank Tabungan Negara (BTN), Tbk. period of 2010-2014. This type of research is quantitatively using simple linear regression analysis techniques with normality test, autocorrelation test, heteroscedasticity test, correlation coefficient, coefficient of determination, t test and F test. The method used is descriptive and verification, with data technique accumulation by documentary study and literature study. The data obtained are secondary data derived from the financial statements PT. Bank Tabungan Negara (BTN), Tbk. period of 2010-2014. The results of this study indicate that Capital Adequacy Ratio (CAR) has a significant positive effect to Profit Changes.